Presentation is loading. Please wait.

Presentation is loading. Please wait.

Question:Consider the expressions: (a)F = XY + XY' (b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' Example For each of.

Similar presentations


Presentation on theme: "Question:Consider the expressions: (a)F = XY + XY' (b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' Example For each of."— Presentation transcript:

1 Question:Consider the expressions: (a)F = XY + XY' (b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' Example For each of these expressions, 1i.Build the truth table ii.Implement the logic circuit 2i.Simplify the expression using theorems of Boolean Algebra ii.Build the truth table (of the simplified expression) iii.Implement the logic circuit 3Simplify the expression using Karnaugh map

2 Question:(a)F = XY + XY' 1ii.Implement the logic circuit 1i.Build the truth table XYF000010101111XYF000010101111 X Y Y' XY XY' F = XY + XY'

3 Question:(a)F = XY + XY' 2ii.Build the truth table (of the simplified expression) 2i.Simplify the expression using theorems of Boolean Algebra F=XY + XY' =X(Y + Y') =X. 1 =X XYF0x01x1XYF0x01x1 2iii.Implement the logic circuit XF = X

4 Question:(a)F = XY + XY' 3Simplify the expression using Karnaugh map 0 X Y 0 11 01 0 1 F=XF=X

5 Question:(b) B = XYZ + XYZ' + X'Y'Z + X'Y'Z' 1i.Build the truth table XYZB00010011010001101000101011011111XYZB00010011010001101000101011011111

6 Question: (b) B = XYZ + XYZ' + X'Y'Z + X'Y'Z' 1ii.Implement the logic circuit XYZ X'Y'Z' B = XYZ + XYZ' + X'Y'Z + X'Y'Z' XYZ XYZ' X'Y'Z X'Y'Z'

7 Question:(b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' 2ii.Build the truth table (of the simplified expression) 2i.Simplify the expression using theorems of Boolean Algebra B=XYZ + XYZ' + X'Y'Z + X'Y'Z' =XY(Z + Z') + X'Y'(Z + Z') =XY + X'Y' XYZB00x101x010x011x1XYZB00x101x010x011x1

8 2iii.Implement the logic circuit Question:(b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' X Y Y' XY X'Y' B = XY + X'Y' X' 3Simplify the expression using Karnaugh map B=X'Y' + XY 1 X YZ 1 00 0001 0 1 00 11 1110

9 Question: (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' 1i.Build the truth table WXYZB00001000100010100110010010101001101011101000010010101001011011000110101110011110WXYZB00001000100010100110010010101001101011101000010010101001011011000110101110011110

10 Question: (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' 1ii.Implement the logic circuit

11 Question: (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' 2ii.Build the truth table (of the simplified expression) 2i.Simplify the expression using theorems of Boolean Algebra D=W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' =W'Z'(X'Y' + X'Y + XY' + XY) =W'Z'((X'(Y' + Y) + X(Y' + Y)) =W'Z'(X' + X) =W'Z' WXYZD0xx010xx101xx001xx10WXYZD0xx010xx101xx001xx10

12 2iii.Implement the logic circuit Question: (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' 3Simplify the expression using Karnaugh map D=W'Z' W Z 1 WX YZ 0 01 0001 00 01 01 10 1110 00 00 11 10 00 00


Download ppt "Question:Consider the expressions: (a)F = XY + XY' (b)B = XYZ + XYZ' + X'Y'Z + X'Y'Z' (c)D = W'X'Y'Z' + W'X'YZ' + W'XY'Z' + W'XYZ' Example For each of."

Similar presentations


Ads by Google